Quantization of the electromagnetic field outside static black holes and its application to low-energy phenomena - Crispino, Luis C. B. [UNESP]; Higuchi, Atsushi; Matsas, George E. A. (American Physical Society (APS), 2001)
We discuss the Gupta-Bleuler quantization of the free electromagnetic field outside static black holes in the Boulware vacuum. We use a gauge which reduces to the Feynman gauge in Minkowski spacetime. We also discuss its relation with gauges used previously. Then we apply the low-energy sector of this field theory to investigate some low-energy phenomena. First, we discuss the response rate of a static charge outside the Schwarzschild black hole in four dimensions. Next, motivated by string physics, we compute the absorption cross sections of low-energy plane waves for the Schwarzschild and extreme Reissner-Nordström black holes in arbitrary dimensions higher than three. ©2001 The American Physical Society.